Diurnal effects on spearmint oil yields and composition - Bufalo, Jennifer [UNESP]; Zheljazkov, Valtcho D.; Cantrell, Charles L.; Astatkie, Tess; Ciampa, Lyn; Jeliazkova, Ekaterina (Elsevier B.V., 2015)
'Native'spearmint (Mentha spicata L.) is one of the two spearmint species grown commercially in the United States and other countries for essential oil production. The two major constituents of spearmint oil are carvone and limonene. It is not known if the essential oil yield (content) and composition of spearmint oil are affected by diurnal variation, and when it would be the best time for harvesting flowering spearmints within a 24h period. Therefore, the objective of this study was to evaluate the effect of diurnal variation on yield and composition of spearmint 'Native'essential oil for the environmental conditions of Northern Wyoming, at elevation 1170 m above the sea level. The experiment was conducted on a 3-year old well established spearmint plantation. The harvest times were every 2 h within a 24-h period: 7:00 AM, 9:00 AM, 11:00AM, 1:00 PM, 3:00 PM, 5:00 PM, 7:00 PM, 9:00 PM, 11:00 PM, 1:00 AM, 3:00 AM, and 5:00 AM. Essential oil yield varied from 0.96 to 1.47 g of oil per 100 g of dry herbage; the maximum oil yield was obtained at 9:00 AM and the minimum at 7:00 PM. The concentration of carvone in the oil varied from 44.1% (at 1:00 PM) to 66.4% (at 9:00 PM) of the total oil. However, the yield of carvone (a function of oil yield and carvone concentration in the oil) was the highest at 3:00 AM and the lowest at 1:00 PM. The concentration of limonene (10.7-15.8% of the oil) was the highest at 7:00 PM and the lowest at 1:00 PM, whereas the yield of limonene was the highest at 9:00 PM. For best essential oil yields, flowering spearmint should be harvested at around 9:00 AM. However, to obtain oil with high carvone concentration, spearmint should be harvested at 9:00 PM. Harvests at 1:00 PM would result in spearmint oil with low concentrations of both carvone and limonene, and hence, should be avoided. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Mentha spicata L; Diurnal changes; Essential oil yield; Essential oil composition; Carvone